Dimensi Kepribadian Kobayashi Makoto dalam Film Colorful melalui Teori Big Five Personality - Oktaviani, Diah Ayu; Winingsih, Irma (Vocational College of Diponegoro University, 2026)
This study aims to describe the personality of Kobayashi Makoto, the main character in Keiichi Hara’s Colorful (2010), using Paul T. Costa Jr. and Robert R. McCrae’s Big Five Personality (OCEAN) model. This research employs a descriptive qualitative method with observation and note-taking techniques. The findings reveal that three of Makoto’s personality dimensions, Openness to Experience, Conscientiousness, and Extraversion are dynamic and show positive development throughout the narrative. The Agreeableness dimension also exhibits minor improvement, reflected in Makoto’s gradual reduction of defensiveness and increased willingness to form healthier interpersonal connections. Meanwhile, the Neuroticism dimension remains relatively stagnant at a high level, indicating enduring emotional instability rooted in past trauma. These results suggest that Colorful portrays not only a spiritual journey but also the psychological process of adolescence in confronting emotional wounds, discovering life’s meaning, and rebuilding a sense of self and relational responsibility.